Los modelos DSGE: una respuesta de la discusión macroeconómica. (2011)
Models of Dynamic Stochastic General Equilibrium (DSGE) are based on the theory of general equilibrium that influences contemporary macroeconomics. This instrument explains the aggregate economic phenomena derived from microeconomic principles, and, as a special characteristic, the DSGE models are not vulnerable to the Lucas critique. Also, those consider that the economy is affected by random shocks. In this sense, empirical analysis seeks for the sources of economic fluctuations. This paper presents an overview of the theoretical literature on economic fluctuations in order to reflect on the development of modern macroeconomics, the reflection culminating with an overview of the DSGE